Health-related quality of life in patients with peripheral nerve tumors: results from the German multicentric Peripheral Nerve Tumor Registry - Grübel, Nadja; Antoniadis, Gregor; AK, Uerschels; Mayer, Benjamin; König, Ralph; Wirtz, Christian Rainer; Pala, Andrej; Dengler, Nora F.; Pedro, Maria Teresa (Frontiers in Oncology, 2024)
Objective: Peripheral nerve tumors (PNT) are rare diseases. So far, no multicenter data on diagnostics, the efficacy of treatment, long-term outcomes, and health-related quality of life (HRQoL) exists. The establishment of the Peripheral Nerve Tumor Registry (PNTR) in 2015 allows for systematic analysis of patients with tumors associated with peripheral nerves. The present study aims to investigate the impact of PNT on an individual's HRQoL and the effect of surgery.Methods: HRQoL was pre-and postoperatively assessed by the Euro-Qol-5D-5L (EQ-5D-5L) and Euro-Qol visual analog scale (EQ-VAS) survey in the retrospective and prospective study arm in three active participating study centers. An index was calculated based upon the EQ-5D-5L for quantification of health state (0: worst possible state of health, 1: best possible state of health). The EQ-VAS ranges from 0 (worst imaginable health status) to 100 % (best possible health status). Patient characteristics (age, sex), as well as disease (histopathological entity) and treatment (pre-and postoperative symptoms, type of treatment) specific data, were analyzed.Results: Data from 171 patients from three high-volume centers were included, with schwannoma (70.8%, n=121) and neurofibroma (15.8%, n=27) being the most prevalent histopathological diagnoses.Both the median health index value (preoperative: 0.887, n=167; postoperatively: 0.910, n=166) and the median EQ-VAS (preoperative 75%, n=167; postoperatively 85%, n=166) of the entire cohort, regarding all histopathological diagnosis improved significantly after surgical therapy (p<0.001, respectively). Preoperatively, 12.3% (n=21) reached the highest index score of 1.0 in EQ-5D-5L and 100% in the EQ-VAS Score in 5.3% (n=9) of all patients. Postoperatively, the highest index score of 1.0 and 100% in the EQ-VAS Score increased significantly and were achieved in 33.3% (n= 57) and 11.1% (n=19), respectively (p<0.001).For the first time, our study presents multicenter data on life quality and the effect of surgery in primarily benign peripheral nerve tumors. Early surgery at a specialized center could improve neurological outcomes and, in conclusion, better QoL. In summary, surgical therapy significantly improved the entire cohort's QoL, VAS, and analgesia.